Automobile interior part waterproof and scratch-resistant high gloss coating and preparation method thereof

By combining a primer and a high-gloss black topcoat, and utilizing near-infrared radiation and ultraviolet cross-linking technology, the problem of uneven curing of high-gloss coatings for automotive interiors was solved, resulting in improved water resistance, scratch resistance, and adhesion stability, while reducing the thermal load on the substrate.

CN123042618APending Publication Date: 2026-11-06HUANGGANG HUAYI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611563123.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-10-10
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing high-gloss coatings for automotive interiors suffer from uneven curing in the thickness direction and localized areas due to carbon black light absorption and the presence of non-reactive carriers at the pigment interface. Increased UV dose may cause excessive cross-linking of the surface and a decrease in the high-gloss appearance. Conventional hot air curing increases the heat load on the plastic substrate, making it difficult to balance scratch resistance and adhesion stability after water treatment.

Method used

The product employs a combination of primer and high-gloss black topcoat. The primer consists of separately stored components A and B. The high-gloss black topcoat is produced by grinding carbon black using low-viscosity hydroxyl acrylic resin and a UV-curable acrylate grinding carrier. This process combines near-infrared radiation and ultraviolet crosslinking to form a continuous curing process of reactive pre-mixing, near-infrared thermal crosslinking, and ultraviolet crosslinking.

Benefits of technology

It improves the network integrity of the carbon black interface and the deep layer of the topcoat, reduces the curing difference in the film thickness direction, improves the water resistance, scratch resistance and environmental stability of the coating, reduces the heat load of the substrate and the duration of high temperature, and maintains a high-gloss appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123042618A_ABST
    Figure CN123042618A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of automobile interior coating, and discloses a waterproof and scratch-resistant high-gloss coating for automobile interior parts and a preparation method thereof. The coating comprises a primer and a high-gloss black finish paint. The high-gloss black finish paint contains a reaction type carbon black abrasive formed by jointly grinding carbon black, low-viscosity hydroxyl acrylic resin, UV-curable acrylic ester grinding carrier, a high-molecular dispersant, partial dipropylene glycol diacrylate and butyl acetate, and is matched with aliphatic polyisocyanate. In the coating preparation process, the hydroxyl group and the isocyanate group are first crosslinked by near-infrared irradiation, and then are sequentially subjected to 365nm and 395nm ultraviolet curing. The application is favorable for reducing the curing difference in the thickness direction and the pigment interface of the carbon black-containing finish paint, and improving the adhesion and the wear-resistant gloss retention rate after water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of automotive interior coating technology, and in particular to a waterproof, scratch-resistant, high-gloss coating for automotive interior parts and its preparation method. Background Technology

[0002] As automotive interior parts demand higher levels of both aesthetics and durability, piano black and high-gloss black coatings are widely used on plastic components such as center consoles, dashboards, and door panels. These coatings not only need to have high gloss, blackness, and reflectivity, but also need to maintain good adhesion and appearance stability after contact with water, detergents, sunscreen, or scratches.

[0003] To improve production efficiency and coating hardness, existing high-gloss black coatings typically employ ultraviolet (UV) curing systems. These systems offer fast curing speeds and short production cycles, making them suitable for continuous coating of automotive interior plastic parts. However, carbon black absorbs UV light, which can lead to uneven curing energy across the coating surface, deeper layers, and areas rich in carbon black, resulting in localized insufficient curing. Increasing UV irradiation energy or extending the irradiation time may cause excessively rapid surface curing, shrinkage, and increased internal stress, affecting leveling and the high-gloss appearance.

[0004] To address the issue of insufficient curing in black or colored UV-cured coatings, existing technologies typically employ a dual curing system combining photocuring and thermal curing. For example, Chinese invention patent CN108997925A discloses a colored dual-curing UV coating for automotive interior parts, which uses hydroxyl-containing polyurethane acrylic resin, aliphatic polyurethane acrylic resins with different functionalities, various photoinitiators, and high-pigment carbon black paste, with isocyanate curing agent added to the coating. During coating preparation, the coating is first heated at 60-80℃, followed by UV curing. Chinese invention patent CN111534213A discloses a dual-curing high-gloss coating for automotive interiors, its preparation method, and its application. This dual-curing high-gloss coating for automotive interiors, composed of hydroxyl-containing polyurethane acrylic resin, high-functionality polyurethane acrylic resin, and isocyanate-containing resin, is cured by UV light and subsequently dried.

[0005] However, existing technologies mainly improve the curing degree of carbon black-containing coatings by compounding photoinitiators with different absorption bands and combining them with overall heating. However, the improvement on the curing of carbon black pigment interfaces and deep layers of coatings is still relatively limited. On the one hand, carbon black is usually added to the coating in the form of pre-made black paste. The grinding carrier and dispersing components in the paste are mainly used for wetting, dispersing and stabilizing the carbon black. Some components are difficult to fully participate in subsequent cross-linking, which can easily lead to the formation of areas with relatively low cross-linking degree around the carbon black particles. This results in water absorption, swelling, decreased adhesion and scratch resistance after the coating is treated with water or subjected to external forces. On the other hand, existing ovens or hot air heating require simultaneous heating of the coating, plastic substrate and tooling. This has problems such as slow heating rate, high energy consumption and uneven temperature control. It may also subject the plastic substrate to a large overall heat load, increasing the risk of substrate softening or deformation. Summary of the Invention

[0006] The technical problem to be solved by this invention is that carbon black-containing high-gloss coatings for automotive interior parts are prone to uneven curing in the thickness direction and local areas due to the light absorption of carbon black and the presence of non-reactive carriers at the pigment interface. Increasing the UV dose may cause excessive cross-linking of the surface and a decrease in the high-gloss appearance, while conventional hot air curing will increase the overall heat load of the plastic substrate. Therefore, it is difficult to maintain the high-gloss appearance while taking into account scratch resistance and adhesion stability after water treatment. To address this, we propose a waterproof and scratch-resistant high-gloss coating for automotive interior parts and its preparation method.

[0007] This invention proposes a waterproof, scratch-resistant, high-gloss coating for automotive interior parts, comprising a primer and a high-gloss black topcoat.

[0008] The primer comprises separately stored primer component A and primer component B. By weight, primer component A comprises 25-45 parts hydroxyl acrylic resin, 15-30 parts difunctional aliphatic polyurethane acrylate, 8-18 parts dipropylene glycol diacrylate, 1.0-3.0 parts TPO-L, 0.3-1.2 parts photoinitiator 184, 0.5-3.0 parts adhesion promoter, 0.1-0.6 parts leveling agent, 0.05-0.5 parts defoamer, and 10-25 parts butyl acetate. The sum of the weight parts of all raw materials in primer component A is 100 parts. Based on 100 parts by weight of primer component A, primer component B comprises 5-12 parts by weight hexamethylene diisocyanate trimer.

[0009] The high-gloss black topcoat comprises component A and component B. By weight, component A of the high-gloss black topcoat comprises: 12-25 parts of hexafunctional aliphatic polyurethane acrylate, 18-35 parts of difunctional aliphatic polyurethane acrylate, 5-15 parts of hydroxyl-functional aliphatic polyurethane acrylate, 1.5-4.5 parts of carbon black, 2-8 parts of low-viscosity hydroxyl acrylic resin, 0.5-3 parts of UV-curable acrylate grinding carrier, 0.3-1.5 parts of carbon black-specific polymeric dispersant, 6- 16 parts DPGDA, 3-10 parts HDDA, 1-6 parts TMPTA, 1.5-3.0 parts TPO-L, 0.3-1.2 parts photoinitiator 184, 0.1-0.6 parts leveling agent, 0.05-0.5 parts defoamer, 0.1-1.0 parts scratch-resistant wax, 0.02-0.15 parts bismuth catalyst, and 5-20 parts butyl acetate; per 100 parts by weight of component A of the high-gloss black topcoat, component B includes 2-12 parts by weight of aliphatic polyisocyanate.

[0010] In one embodiment, the hexafunctional aliphatic polyurethane acrylate is EBECRYL® 1290 manufactured by ZXTech, which is an aliphatic polyurethane hexaacrylate oligomer with an average acrylate functionality of 6. This product is not pre-diluted with reactive diluents, and has a typical viscosity of approximately 85,000 mPa·s at 25°C, a typical viscosity of approximately 2,040 mPa·s at 60°C, and a typical density of approximately 1.19 g / mL at 25°C. Its cured film has high hardness and scratch resistance.

[0011] In one embodiment, the difunctional aliphatic polyurethane acrylate is EBECRYL® 8402 manufactured by ZXTech, which is an aliphatic polyurethane diacrylate oligomer with an average acrylate functionality of 2. This product is not pre-diluted with reactive diluents, and has a typical viscosity of approximately 14830 mPa·s at 25°C, a typical viscosity of approximately 507 mPa·s at 60°C, a typical density of approximately 1.12 g / mL at 25°C, a typical glass transition temperature of approximately 14°C for the cured product, and an elongation at break of approximately 50%.

[0012] In one embodiment, the primer hydroxy acrylic resin is SETALUX® 1211BA-65 produced by Zhanxin Company. It is a hydroxy acrylic polyol resin solution with butyl acetate as solvent, with a non-volatile content of about 65%, a hydroxyl content of about 3.0% based on non-volatile content, a typical viscosity of about 2.0 Pa·s at 23°C, and a maximum color of about 35 APHA.

[0013] Preferably, the hydroxyl-functional aliphatic polyurethane acrylate is a hydroxyl-functional aliphatic polyurethane acrylate oligomer containing both hydroxyl groups and free radical polymerizable acrylate groups, with a solid content of 55%-65%, a hydroxyl value of 20-40 mgKOH / g, and a viscosity of 1000-2500 mPa·s at 25°C.

[0014] In one embodiment, EBECREL®4900, manufactured by ZENXIN, is used. It is a hydroxyl-functional aliphatic polyurethane acrylate oligomer diluted with butyl acetate, with a solid content of about 60%, a hydroxyl value of about 28 mg KOH / g, and a viscosity of about 1500 mPa·s at 25°C.

[0015] Preferably, the low-viscosity hydroxyl acrylic resin is an acrylic copolymer resin solution containing side-chain hydroxyl groups, using butyl acetate as a solvent, with a non-volatile content of 63%-67%, a hydroxyl content of 2.8-3.2% based on non-volatile matter, a viscosity of 1.5-3.0 Pa·s at 23-25°C, and an acid value of 4-8 mgKOH / g. In one embodiment, SETALUX 1211BA-65 is used, with a non-volatile content of 65%, a hydroxyl content of 3.0%, a viscosity of approximately 2.0 Pa·s at 23°C, and an acid value of approximately 6.5 mgKOH / g. This resin plays a role in polymer carrying and compatibility during the carbon black grinding stage and undergoes thermal crosslinking with aliphatic polyisocyanate during the near-infrared treatment stage.

[0016] Preferably, the UV-curable acrylate grinding carrier is a low-viscosity acrylate grinding carrier containing two free radical polymerizable acrylate groups, a solid content of not less than 98%, and a viscosity of 80-250 mPa·s at 25°C; in one embodiment, EBECRYL 151 modified diacrylate is used, which has a viscosity of about 125 mPa·s at 25°C, making it suitable for forming a low-viscosity pigment dispersion using a bead mill, and capable of participating in photocrosslinking during the subsequent UV irradiation stage.

[0017] Preferably, the carbon black is high-pigment gas-processed carbon black with an average primary particle size of 18-30 nm and an oil absorption value of 90-130 mL / 100 g.

[0018] In one embodiment, the high-pigment carbon black is SPECIAL BLACK® 4 manufactured by Orion, which is a post-treated, regularized color gas-processed carbon black with an average primary particle size of approximately 25 nm, an oil absorption value of approximately 115 mL / 100 g, and a BET specific surface area of ​​approximately 180 m². 2 / g, pH value is about 3, typical blackness MY is 244.

[0019] Preferably, the carbon black-specific polymeric dispersant is a solvent-free polymeric wetting and dispersing agent containing pigment affinity groups, and its dosage is 20-40% of the carbon black mass. In a specific embodiment, DISPERBYK-2118 is used for medium polar to non-polar solvent-based or solvent-free pigment concentrates and for dispersing carbon black.

[0020] Preferably, the DPGDA is dipropylene glycol diacrylate, CAS number 57472-68-1, a difunctional reactive diluent used as a reactive grinding medium in reactive carbon black pastes and entering the photocrosslinking network under ultraviolet irradiation; the HDDA is 1,6-hexanediol diacrylate, CAS number 13048-33-4, a difunctional reactive diluent used to reduce the viscosity of the topcoat and increase the curing speed; and the TMPTA is trimethylolpropane triacrylate, CAS number 15625-89-5, a trifunctional reactive diluent used to improve crosslinking density, surface hardness, and chemical resistance.

[0021] Preferably, TPO-L is ethyl 2,4,6-trimethylbenzoylphenylphosphonate, CAS number 84434-11-7, a liquid type I photoinitiator, mainly used to absorb longer wavelength ultraviolet light and promote deep curing of carbon black-containing coatings; photoinitiator 184 is 1-hydroxycyclohexylphenyl ketone, CAS number 947-19-3, a type I photoinitiator, mainly used to supplement surface curing in shorter wavelength regions; the mass ratio of TPO-L to photoinitiator 184 is 1.5:1-4:1.

[0022] Preferably, the leveling agent is a polyether-modified polydimethylsiloxane type surface additive used to reduce the surface tension of the coating and improve leveling and clarity. In a specific embodiment, BYK-333 is used.

[0023] Preferably, the defoamer is a silicone-free polymer defoamer suitable for solvent-based, high-solids, and radiation-curing systems, used to suppress bubbles generated during paint mixing, spraying, and rapid heating. In a specific embodiment, BYK-1790 is used.

[0024] Preferably, the scratch-resistant wax is micronized polyethylene wax. In this example, CERAFLOUR® 1050 manufactured by BYK is used. This product is based on polyethylene wax, is in solid powder form, has a particle size D90 of about 10 μm, and is suitable for transparent coatings and high-gloss coating systems that are sensitive to haze.

[0025] Preferably, the HDI trimer has an NCO content of 21.5%-22.1%, and component B is added before the application of the high-gloss black topcoat. It is prepared according to the total equivalent of reactive hydroxyl groups in component A, so that the NCO / OH equivalent ratio is 0.90:1-1.05:1.

[0026] In one embodiment, the HDI trimer is Desmodur® ultra N3300 manufactured by Covestro, which is an aliphatic isocyanurate-type polyisocyanate based on hexamethylene diisocyanate. The product has a non-volatile content of approximately 100%, an isocyanate group content of 21.5-22.1%, a dynamic viscosity of 2250-3750 mPa·s at 23°C, a free HDI monomer content of less than 0.10%, a BHT content of less than 10 mg / kg, and an average isocyanate functionality of approximately 3.5.

[0027] Preferably, the adhesion promoter is an acrylate-functionalized oligoamine resin. In one embodiment, EBECRYL® 7100 manufactured by ZNTech is used. This product belongs to the amine-functionalized acrylate co-initiating resin category. Its typical viscosity at 25°C is about 1200 mPa·s, and its typical amine value is about 140 mg KOH / g. It can participate in UV curing and improve the adhesion of the coating to ABS and polycarbonate plastic substrates.

[0028] Preferably, the bismuth catalyst is Borchi® Kat 24 manufactured by Borchers, which is a solvent-free organic bismuth catalyst with bismuth 2-ethylhexanoate as the main component, a bismuth content of about 24%, and no organotin, used to promote the polyurethane crosslinking reaction between hydroxyl groups and isocyanate groups.

[0029] This invention proposes a method for preparing a waterproof, scratch-resistant, high-gloss coating for automotive interior parts, comprising the following steps:

[0030] S1: According to the formulation of component A of the high-gloss black topcoat, add low-viscosity hydroxyl acrylic resin, UV-curable acrylate grinding carrier, carbon black-specific polymeric dispersant, part of DPGDA and part of butyl acetate into a dispersion container, and stir at 600-1000 r / min for 10-20 min to obtain the grinding base; under stirring conditions of 1000-1500 r / min, add carbon black in batches to the grinding base, and after the addition is complete, pre-disperse at 1500-2500 r / min for 20-40 min to obtain carbon black pre-dispersion; transfer the carbon black pre-dispersion to a sand mill with a cooling jacket, and grind it using zirconia beads with a diameter of 0.6-0.8 mm.

[0031] S2: Add 6-functional aliphatic polyurethane acrylate, 2-functional aliphatic polyurethane acrylate and hydroxyl-functional aliphatic polyurethane acrylate to the carbon black grinding material obtained in step S1, and stir at 400-800 r / min for 15-30 min. Add the remaining DPGDA, HDDA and TMPTA, and stir at 500-900 r / min for 10-20 min. Dissolve photoinitiator 184 in the reserved portion of DPGDA, and then add TPO-L to mix and obtain a photoinitiator premix. Add the photoinitiator premix to the above materials and stir at 400-800 r / min for 10-20 min. Add leveling agent, defoamer, scratch-resistant wax and bismuth catalyst in sequence, and stir at 400-700 r / min for 10-20 min. Then add the remaining butyl acetate to adjust the viscosity. After standing to remove bubbles, filter through a 300-mesh filter to obtain high-gloss black topcoat component A.

[0032] S3: Mix high-gloss black topcoat component A and high-gloss black topcoat component B, stir at 300-500 r / min for 3-5 min, let stand to degas for 5-10 min, and obtain high-gloss black topcoat.

[0033] S4: Add hydroxyl acrylic resin, difunctional aliphatic polyurethane acrylate and part of DPGDA to a paint mixing container, and stir at 400-800 r / min for 15-25 min to obtain a primer resin mixture; dissolve photoinitiator 184 in the remaining DPGDA, then add TPO-L and mix to obtain a primer photoinitiator premix; add the primer photoinitiator premix to the primer resin mixture, and stir at 400-700 r / min for 10-20 min; add adhesion promoter, leveling agent and defoamer in sequence, stir evenly, add butyl acetate to adjust the viscosity, let stand to degas and filter through a 300 mesh filter to obtain primer component A.

[0034] S5: Mix primer component A and primer component B, stir at 300-500 r / min for 3-5 min, let stand to degas for 5-10 min, and obtain an applicable primer.

[0035] S6: Dust removal, oil removal and cleaning treatment of automotive interior plastic substrate. Spray the primer obtained in step S5 onto the substrate surface, and control the dry film thickness of the primer to be 10-15μm. After spraying, level at 20-30℃ for 5-10min, then heat treat at 60-75℃ for 5-10min, and then perform UV pre-curing after cooling.

[0036] S7: Spray the high-gloss black topcoat obtained in step S3 onto the substrate surface treated with primer, and control the dry film thickness of the high-gloss black topcoat to be 25-35μm; after spraying, level it at 20-30℃ for 5-10min, and then flash dry it at 45-60℃ for 3-8min.

[0037] S8: After flash-drying, the high-gloss black topcoat is subjected to near-infrared irradiation to raise the surface temperature of the coating to 75-90℃ and maintain it for 60-120 seconds; after the near-infrared treatment, ultraviolet curing is performed, with a total ultraviolet irradiation energy of 900-1800 mJ / cm². 2 After UV curing, the coating is placed in an environment of 23±2℃ and 50%±5% relative humidity for 24 hours to obtain a waterproof, scratch-resistant, high-gloss coating for automotive interior parts.

[0038] Preferably, the DPGDA used in step S1 is 40-60% of the total DPGDA content in component A of the high-gloss black topcoat, and the butyl acetate used is 30-50% of the total butyl acetate content in component A of the high-gloss black topcoat.

[0039] Preferably, in step S1, during the pre-dispersion process, circulating cooling water is introduced into the cooling jacket of the dispersion container to control the temperature of the carbon black pre-dispersion material to be no higher than 45°C; during the grinding process, circulating cooling water is introduced into the cooling jacket of the sand mill to control the temperature of the carbon black pre-dispersion material to be 30-45°C, and the grinding is carried out until the scraper fineness is no greater than 5μm; during the sand milling process, the filling volume of the zirconia beads is preferably 60%-75% of the effective volume of the grinding chamber of the sand mill, and the linear speed of the grinding rotor is preferably 8-12m / s.

[0040] Preferably, in step S2, the remaining DPGDA and remaining butyl acetate are added, wherein the DPGDA used to dissolve the photoinitiator 184 is reserved from the total amount of DPGDA to be added in step S2, reserving 10-20% of the total amount of DPGDA, and is not added separately.

[0041] Preferably, in step S4, 70%-85% of the total DPGDA content in primer component A is added first, and the remaining DPGDA is used to dissolve photoinitiator 184.

[0042] Preferably, the photoinitiator 184 is dissolved at 35-45°C; the preparation and addition of the photoinitiator premix should avoid exposure to sunlight and strong ultraviolet light.

[0043] Preferably, the outflow time of component A of the high-gloss black topcoat, measured at 25°C using a DIN 4 cup, is 18-25 s, and the outflow time of component A of the primer, measured under the same conditions, is 16-23 s.

[0044] Preferably, the high-gloss black topcoat component A and the primer component A should be stored in light-proof, airtight containers, and the coating after mixing components A and B should be used up within 2 hours at 20-30°C.

[0045] Preferably, in step S6, the primer UV pre-curing involves first irradiating it with 365nm UV light to an irradiation energy of 200-400mJ / cm².2 Then, irradiate with 395nm ultraviolet light to an irradiation energy of 300-600mJ / cm. 2 .

[0046] Preferably, in step S8, the near-infrared processing uses a near-infrared device with an effective radiation band of 800-1200nm, and within 30s after the near-infrared processing is completed, it is sequentially irradiated with 365nm and 395nm ultraviolet light sources in segments.

[0047] The technical effects and advantages of this invention are as follows:

[0048] This invention uses a primer to form an adhesion base between the automotive interior plastic substrate and the high-gloss black topcoat. Low-viscosity hydroxyl acrylic resin and a UV-curable acrylate abrasive carrier are used together for carbon black abrasion, ensuring full contact between the two reactive carriers and the carbon black particles and their interfaces. After coating, the topcoat is rapidly heated by the absorption of near-infrared radiation by the carbon black, promoting thermal cross-linking of hydroxyl and isocyanate groups. Then, 365nm and 395nm ultraviolet light are sequentially applied to induce photocross-linking of the acrylate groups. This forms a continuous curing process of pigment interface reactive pre-configuration – near-infrared thermal cross-linking – ultraviolet light cross-linking, which improves the network integrity of the carbon black interface and the deeper layers of the topcoat, reduces curing differences in the film thickness direction, and improves the coating's water resistance, scratch resistance, and environmental stability.

[0049] Experimental results show that, under the same final chemical composition, the double bond conversion rate, gel fraction, and gloss retention rate after boiling are all higher when reactive resin is used for carbon black grinding than when reactive resin is added after grinding. This indicates that the effect is not caused by a simple change in formulation or pigment fineness. At the same time, under similar initial abrasion resistance and gel fraction, near-infrared treatment can shorten the time for the coating to reach the thermal reaction temperature compared to hot air treatment, and reduce the highest temperature on the back of the substrate, the duration of high temperature, and the warpage increment, thus achieving a balance between the degree of coating curing and the thermal load on the plastic substrate. Attached Figure Description

[0050] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings:

[0051] Figure 1 A comparison chart showing the retention rate of Taber abrasion resistance and gloss before and after boiling in water;

[0052] Figure 2 The ATR-FTIR spectrum of the cured film;

[0053] Figure 3 The DSC curve of the cured film;

[0054] Figure 4 This is a curve showing the change in hardness of the indentation on the cross-section of the topcoat as a function of the film thickness. Detailed Implementation

[0055] In this specification, unless otherwise expressly stated, "at least one" means one or more; "not less than" means greater than or equal to the stated value; "not more than" or "not exceeding" means less than or equal to the stated value; "above," "below," and "within" all include the stated number, while "greater than" and "less than" do not include the stated number; "one or more" means one, two, or more; "optional" means that the listed technical features may or may not be present; the numerical ranges described herein include the endpoints of the range and any values ​​between the endpoints and the sub-ranges formed therefrom; unless otherwise stated, all parts in this specification are parts by weight, and the percentages in the formulation composition and raw material content are mass percentages; when two grinding carriers are involved in proportion, they are calculated according to the mass of their non-volatile components.

[0056] The following preparation examples illustrate the specific preparation process of the raw materials, intermediate products or products involved in this invention, and provide a sample basis for the formulation, performance testing and technical effect verification of subsequent embodiments.

[0057] Preparation Example 1

[0058] Weigh 43.08 parts of low-viscosity hydroxyl acrylic resin, 7.00 parts of UV-curable acrylate grinding carrier, 4.00 parts of carbon black-specific polymeric dispersant, 16.00 parts of DPGDA and 17.92 parts of butyl acetate, add them to a dispersion container with a cooling jacket, and stir at 800 r / min for 15 min to obtain the grinding base.

[0059] Increase the stirring speed to 1200 r / min and add 12.00 parts of high pigment carbon black to the grinding base in batches within 15 min; after the carbon black is added, pre-disperse at 1800 r / min for 30 min. During the pre-dispersion process, 20℃ circulating cooling water is introduced into the cooling jacket of the dispersion container to control the material temperature not to exceed 45℃.

[0060] The obtained carbon black pre-dispersed material was transferred into a horizontal sand mill with a cooling jacket. Zirconia beads with a diameter of 0.7 mm were used, and the filling volume of the zirconia beads was 70% of the effective volume of the grinding chamber. The rotor linear speed was 9 m / s. During the grinding process, circulating cooling water was introduced into the cooling jacket of the sand mill to control the grinding temperature at 35-40℃. The material was circulated and ground until the fineness measured by the scraper fineness gauge was no greater than 5 μm. After filtration through a 300-mesh filter, the carbon black grinding material of Preparation Example 1 was obtained.

[0061] Preparation Example 2

[0062] Except for the amount of low-viscosity hydroxyl acrylic resin (37.69 parts), UV-curable acrylate abrasive carrier (10.50 parts), and butyl acetate (19.81 parts), the composition of other raw materials and preparation conditions were the same as in Preparation Example 1, and carbon black abrasive of Preparation Example 2 was obtained.

[0063] Preparation Example 3

[0064] Except for the amount of low-viscosity hydroxyl acrylic resin (45.77 parts), UV-curable acrylate abrasive carrier (5.25 parts), and butyl acetate (16.98 parts), the composition of other raw materials and preparation conditions were the same as in Preparation Example 1, and carbon black abrasive of Preparation Example 3 was obtained.

[0065] Table 1. Primer A component formulation

[0066]

[0067] Add 35.00 parts of hydroxyl acrylic resin, 18.00 parts of difunctional aliphatic polyurethane acrylate and 10.00 parts of DPGDA to a light-proof paint mixing container and stir at 500 r / min for 15 min to obtain a primer resin mixture.

[0068] Add 1.00 part of photoinitiator 184 to the remaining 2.00 parts of DPGDA, stir at 40°C until dissolved, then add 2.00 parts of TPO-L and mix evenly to obtain the primer photoinitiator premix.

[0069] Add the primer photoinitiator premix to the primer resin mixture and stir at 600 rpm for 15 min; then add 1.00 part of adhesion promoter, 0.30 part of leveling agent and 0.20 part of defoamer in sequence, and continue stirring at 600 rpm for 15 min; add 30.50 parts of butyl acetate, stir at 400 rpm for 10 min, let stand for 15 min to degas, and filter through a 300-mesh filter to obtain primer component A.

[0070] The primer component B is an HDI trimer. The amount of component B added is determined based on the actual total equivalent of hydroxyl groups in primer component A and the actual NCO content of the HDI trimer, so that the NCO / OH equivalent ratio is 1.05:1. Primer component A and primer component B are stirred at 500 r / min for 3 min and allowed to stand for degassing for 5 min to obtain an applicable primer.

[0071] A PC / ABS injection molded board with dimensions of 150mm×100mm×3mm was used as the substrate. The surface of the substrate was wiped twice with a non-woven cloth soaked in isopropyl alcohol and placed at 25℃ for 10 minutes. The primer was then sprayed with an air spray gun with a nozzle diameter of 1.0mm, an atomization pressure of 0.20MPa, and a distance of 20cm between the spray gun and the substrate surface. The dry film thickness of the primer was controlled to be 12±2μm.

[0072] After the primer is applied, level it at 25°C for 8 minutes, then heat-treat it at 70°C for 8 minutes. Cool the coated parts until the surface temperature does not exceed 35°C, and then irradiate them with a 365nm ultraviolet light source with an irradiation energy of 300mJ / cm². 2 Then, it is irradiated with a 395nm ultraviolet light source to an irradiation energy of 500mJ / cm². 2 Complete the UV pre-curing of the primer.

[0073] Example 1

[0074] The high-gloss black topcoat component A of Example 1 was prepared according to the table below. The carbon black, two grinding carriers, dispersant, DPGDA and butyl acetate listed in the table are all components of the high-gloss black topcoat component A, and a portion of them are used first in the carbon black grinding stage.

[0075] Table 2 Formulation of Component A of High-Gloss Black Topcoat in Example 1

[0076]

[0077] Following the procedure of Preparation Example 1, 6.46 parts of low-viscosity hydroxyl acrylic resin, 1.05 parts of UV-curable acrylate grinding carrier, 0.60 parts of carbon black-specific polymeric dispersant, 1.80 parts of high-pigment carbon black, 2.40 parts of DPGDA and 2.69 parts of butyl acetate were pre-dispersed and ground together to obtain the carbon black grinding material used in Example 1.

[0078] The obtained carbon black grinding material was transferred into a light-proof paint mixing container, and 18.00 parts of hexafunctional aliphatic polyurethane acrylate, 24.00 parts of difunctional aliphatic polyurethane acrylate and 8.00 parts of hydroxyl-functional aliphatic polyurethane acrylate were added. The mixture was stirred at 600 r / min for 20 min.

[0079] Reserve 2.00 parts of the remaining 10.00 parts DPGDA for preparing the photoinitiator premix. Add the remaining 8.00 parts DPGDA, 6.00 parts HDDA, and 3.00 parts TMPTA to the paint mixing container and stir at 700 rpm for 15 min.

[0080] Add 0.80 parts of photoinitiator 184 to the reserved 2.00 parts of DPGDA, stir at 40°C until dissolved, then add 2.20 parts of TPO-L and mix evenly to obtain a photoinitiator premix. Slowly add the photoinitiator premix to the paint mixing container and stir at 600 r / min for 15 min.

[0081] Add 0.30 parts of leveling agent, 0.20 parts of defoamer, 0.50 parts of scratch-resistant wax and 0.08 parts of bismuth catalyst in sequence, and stir at 500 r / min for 15 min; add the remaining 11.92 parts of butyl acetate, stir at 400 r / min for 10 min, let stand for degassing for 15 min, and filter through a 300 mesh screen to obtain component A of high-gloss black topcoat.

[0082] Component B of the high-gloss black topcoat is an HDI trimer. Based on the actual total equivalent of hydroxyl groups in the low-viscosity hydroxyl acrylic resin and hydroxyl-functional aliphatic polyurethane acrylate in component A of the high-gloss black topcoat, as well as the actual NCO content of the HDI trimer, the amount of component B to be added is determined so that the NCO / OH equivalent ratio is 1.05:1. Components A and B are stirred at 500 r / min for 3 min, allowed to stand for degassing for 5 min, and sprayed within 2 h.

[0083] High-gloss black topcoat was sprayed onto the substrate surface treated with the above primer. The nozzle diameter was 1.0 mm, the atomization pressure was 0.22 MPa, the distance between the spray gun and the substrate surface was 20 cm, and the dry film thickness of the high-gloss black topcoat was controlled to be 30 ± 2 μm. After spraying, the coating was allowed to level at 25°C for 8 min, and then flash-dried at 55°C for 5 min.

[0084] The topcoat was treated with a near-infrared device with a peak wavelength of 950 nm and an effective radiation band of 800-1200 nm. The surface temperature of the topcoat was monitored by an infrared thermal imager, and the surface temperature was maintained at 82±3℃ for 90 seconds. Within 30 seconds after the near-infrared treatment, the topcoat was irradiated with a 365 nm ultraviolet light source with an irradiation energy of 400 mJ / cm². 2 Then, it is irradiated with a 395nm ultraviolet light source to an irradiation energy of 800mJ / cm. 2 The total ultraviolet radiation energy is 1200 mJ / cm². 2 .

[0085] After UV curing, the coated parts were placed in an environment of 23±2℃ and 50%±5% relative humidity for 24 hours to obtain the waterproof, scratch-resistant, high-gloss coating for automotive interior parts of Example 1.

[0086] Example 2

[0087] Except for using the carbon black abrasive from Preparation Example 2 and ensuring the non-volatile mass ratio of low-viscosity hydroxyl acrylic resin to UV-curable acrylate abrasive carrier is 70:30, the composition, preparation method, primer treatment, spraying parameters, near-infrared treatment, and UV curing conditions of the high-gloss black topcoat are the same as in Example 1. Based on 15 parts of carbon black abrasive, the low-viscosity hydroxyl acrylic resin in Example 2 is 5.65 parts, the UV-curable acrylate abrasive carrier is 1.58 parts, and the total amount of butyl acetate is adjusted to 14.89 parts.

[0088] Example 3

[0089] Except for using the carbon black abrasive from Preparation Example 3 and setting the non-volatile mass ratio of low-viscosity hydroxyl acrylic resin to UV-curable acrylate abrasive carrier to 85:15, all other conditions were the same as in Example 1. Based on 15 parts of carbon black abrasive, the low-viscosity hydroxyl acrylic resin in Example 3 was 6.87 parts, the UV-curable acrylate abrasive carrier was 0.79 parts, and the total amount of butyl acetate was adjusted to 14.46 parts.

[0090] Example 4

[0091] Except for adjusting the near-infrared treatment conditions to make the surface temperature of the topcoat reach 75±3℃ and hold for 120s, the other raw material composition, preparation method, primer treatment, spraying parameters and ultraviolet curing conditions are the same as in Example 1.

[0092] Example 5

[0093] Except for adjusting the near-infrared treatment conditions to make the surface temperature of the topcoat reach 90±3℃ and hold for 60s, the other raw material composition, preparation method, primer treatment, spraying parameters and ultraviolet curing conditions are the same as in Example 1.

[0094] Comparative Example 1

[0095] The final raw material composition and dosage of the high-gloss black topcoat used are the same as in Example 1. The difference is that the low-viscosity hydroxyl acrylic resin and UV-curable acrylate grinding carrier are not added during the carbon black grinding stage. When preparing the carbon black grinding material, only the carbon black-specific polymeric dispersant, DPGDA, a portion of butyl acetate and carbon black are pre-dispersed and ground. After the carbon black grinding is completed, the low-viscosity hydroxyl acrylic resin, UV-curable acrylate grinding carrier and the remaining butyl acetate are added and stirred at 500 r / min for 30 min. Then, the remaining topcoat components are added according to the method in Example 1 to obtain high-gloss black topcoat component A. The obtained high-gloss black topcoat is subjected to near-infrared treatment and ultraviolet curing in sequence. The specific process conditions are the same as in Example 1.

[0096] Comparative Example 2

[0097] A non-reactive thermoplastic acrylic resin was used to replace the low-viscosity hydroxyl acrylic resin and UV-curable acrylate grinding carrier in Example 1. The non-reactive thermoplastic acrylic resin used was Elvacite manufactured by Mitsubishi Chemical Corporation. TM In 2013, specifically, 53.85 parts of non-reactive thermoplastic acrylic resin were used as the carbon black grinding carrier, and the amount of butyl acetate was adjusted to 14.15 parts; the raw material composition, grinding conditions, and other components of the high-gloss black topcoat of the remaining carbon black grinding material were the same as in Example 1. The non-reactive thermoplastic acrylic resin did not contain any effective hydroxyl groups that could participate in the crosslinking of isocyanates, nor did it contain any acrylate groups that could participate in ultraviolet curing. The resulting high-gloss black topcoat was subjected to near-infrared treatment and ultraviolet curing in sequence, and the specific process conditions were the same as in Example 1.

[0098] Comparative Example 3

[0099] The carbon black abrasive and high-gloss black topcoat formulations used were the same as those in Example 1. The only difference was that hot air treatment was used instead of near-infrared treatment. After the topcoat was leveled and flash-dried, it was hot-air treated at 82°C for 10 minutes, and then UV-cured under the same UV irradiation conditions as in Example 1.

[0100] Comparative Example 4

[0101] The carbon black abrasive and high-gloss black topcoat formulation used are the same as in Example 1. The only difference is that the order of near-infrared treatment and ultraviolet curing is changed. After the topcoat is leveled and flash-dryed, it is first cured under the ultraviolet irradiation conditions of Example 1, and then subjected to near-infrared treatment to make the surface temperature of the topcoat reach 82°C and hold for 90 seconds. No second ultraviolet irradiation is performed after the near-infrared treatment.

[0102] Comparative Example 5

[0103] The carbon black abrasive and high-gloss black topcoat formulations used were the same as in Example 1, except that near-infrared treatment was omitted. After the topcoat leveled and flash-dried, it was directly cured with ultraviolet light, and the total ultraviolet irradiation energy was 1200 mJ / cm². 2 After curing, it will not undergo near-infrared or hot air treatment.

[0104] Comparative Example 6

[0105] The carbon black abrasive and high-gloss black topcoat component A used were the same as in Example 1, but HDI trimer, which is the component B of the high-gloss black topcoat, was not added. After stirring and degassing the high-gloss black topcoat component A, it was directly sprayed, and then near-infrared treatment and ultraviolet curing were performed in the same conditions as in Example 1.

[0106] Comparative Example 7

[0107] Only low-viscosity hydroxyl acrylic resin was used as the carbon black grinding carrier, without adding UV-curable acrylate grinding carrier. Specifically, 53.85 parts of low-viscosity hydroxyl acrylic resin were used in the carbon black grinding material, and the amount of butyl acetate was adjusted to 14.15 parts. The composition of other raw materials and grinding conditions were the same as in Example 1. After grinding, the remaining topcoat components were added according to the method in Example 1 to obtain high-gloss black topcoat component A. Since the amount of low-viscosity hydroxyl acrylic resin changed, the amount of HDI trimer added was adjusted according to the actual hydroxyl content of high-gloss black topcoat component A to make the molar ratio of isocyanate groups to hydroxyl groups the same as in Example 1. The obtained high-gloss black topcoat was subjected to near-infrared treatment and ultraviolet curing in sequence, and the specific process conditions were the same as in Example 1.

[0108] Comparative Example 8

[0109] This comparative example selects a representative formulation based on the raw material range and usage method disclosed in CN108997925A. The UV coating, by weight, includes 24 parts tetrafunctional hydroxyl polyurethane acrylic resin, 20 parts tetrafunctional aliphatic polyurethane acrylic resin, 10 parts trifunctional aliphatic polyurethane acrylic resin, 12 parts hexafunctional aliphatic polyurethane acrylic resin, 12 parts TMPTA, 2 parts photoinitiator 184, 1.5 parts TPO, 2 parts 907, 0.5 parts leveling agent, 4 parts prior art black paste with a carbon black content of 10%, 5 parts ethyl acetate, and 17 parts butyl acetate. The UV coating, a curing agent consisting of 72 parts HDI trimer and 22 parts butyl acetate, and a thinner consisting of equal masses of ethyl acetate and butyl acetate were mixed at a mass ratio of 5:1:2. To reduce the influence of differences between the substrate and primer on the comparison results, Comparative Example 8 and Example 1 used the same batch of PC / ABS substrate and the same transparent primer. The dry film thickness of the topcoat was controlled at 30±2μm. After spraying, the coating was leveled at 25°C for 5 minutes, kept in a 60°C hot air chamber for 10 minutes, and then UV cured using a 395nm LED light source with an irradiation energy of 1200mJ / cm². 2 .

[0110] Experimental Example 1

[0111] The dry film thickness of the primer and topcoat was measured using a cross-sectional microscope. Three cross-sections were cut from each test panel, and five points were measured at each section. The primer thickness of all test panels was controlled at 12±2μm, and the topcoat thickness was controlled at 30±2μm. Gloss was measured using a 60° gloss meter, with five points measured for each test panel. The DOI (Distinctive Image Index) was obtained by measuring three points in the center of the test panel using a vividness meter. The DOI represents the image sharpness of the coating surface and is used to characterize the coating's ability to reproduce details of reflected images. The L* (Lightness Value) was measured using a spectrophotometer under a D65 light source, a 10° observer, and SCI mode. The L* represents the lightness value in the CIELAB color space; the lower the value, the higher the blackness of the coating. The pencil hardness test was conducted using a 750g load and a 45° angled advancement method. Initial adhesion was tested by cutting 100 grids with a 1mm spacing cross-cutting knife, applying pressure-sensitive adhesive tape, and rapidly peeling it off at a 180° angle. The results were recorded as 0-5, with 0 being no peeling.

[0112] Taber abrasion resistance was tested using a CS-10F grinding wheel with a single wheel load of 500g and 100 revolutions. The 60° gloss was measured at five fixed points before and after abrasion. The gloss retention rate was the ratio of the gloss after abrasion to the gloss before abrasion. For steel wool scratch resistance, No. 0000 steel wool was used. Under a 500g load, with a stroke of 100mm and a reciprocating motion of 60 times / min for 20 cycles, the 60° gloss retention rate after scratching was calculated. The results are shown in Table 3. The gloss retention rates of Taber abrasion resistance before and after boiling in Example 1, Comparative Examples 1-4, and Comparative Example 8 are shown in Table 3. Figure 1 As shown.

[0113] Table 3 Initial appearance and scratch resistance

[0114]

[0115] For the boiling water test, the test panel was completely immersed in deionized water at 100±1℃ for 2 hours, then removed, dried, and placed at 23℃ for 2 hours. The gloss retention rate of the boiled test panel was then determined according to the Taber conditions described above. For the constant temperature and humidity test, the test panel was kept at 85℃ and 85% relative humidity for 240 hours. After a 2-hour recovery period, the appearance was observed and the adhesion was tested. For the ethanol resistance test, a cotton cloth soaked in 75% ethanol was used. The cloth was rubbed 500 times under a 500g load, and the gloss retention rate was recorded. For the hot and cold cycling test, one cycle consisted of holding the sample at -40℃ for 2 hours, 23℃ for 0.5 hours, 80℃ for 2 hours, and 23℃ for 0.5 hours, for a total of 10 cycles. The adhesion was then tested.

[0116] The substrate heat load test was conducted by monitoring the temperature on the coating surface using an infrared thermal imager. A K-type thermocouple with a diameter of 0.2 mm was attached to the center of the back of the test panel, and the back temperature was recorded at a frequency of 10 Hz. The highest temperature on the back of the substrate during the curing stage and the cumulative time when the back temperature was above 50°C were recorded. Before and after curing, the test panel was placed on a granite platform, and the difference in the maximum height of the four corners from the platform was measured using a feeler gauge as the warpage increment. The results are shown in Table 4.

[0117] Table 4 Water resistance and environmental stability

[0118]

[0119] As can be seen from Tables 3 and 4, the 60° gloss of Examples 1-5 is not lower than 96.2, and the DOI is 87-91. When Example 5 uses a higher near-infrared temperature of 90±3℃, the DOI drops to 87, and after boiling, slight haze appears at the edge, and the warpage increase increases to 0.20mm. This indicates that excessively high near-infrared temperatures will cause the liquid film to thicken faster and increase the heat load on the substrate. Example 4 can still obtain acceptable performance when treated at 75±3℃ for 120s, but the Taber retention rate is slightly lower after boiling. Therefore, 82±3℃ for 90s shows a better balance between appearance, curing and treatment time.

[0120] Example 1 and Comparative Example 1 had the same final resin, carbon black, dispersant, and curing agent composition, the only difference being whether the low-viscosity hydroxyl acrylic resin and UV-curable acrylate grinding carrier were added during the carbon black grinding stage or after grinding. The Taber retention rate after boiling in water in Example 1 was 83.7%, while that in Comparative Example 1 was 72.8%. The initial Taber and steel wool gloss retention rates in Example 1 were also increased by 6.2 percentage points and 5.0 percentage points, respectively. These results indicate that adding the same reactive resin only after the paint mixing stage cannot achieve the same post-water treatment performance as adding it during the grinding stage. Ensuring sufficient contact between the reactive resin and carbon black during the grinding process is an important condition for producing the desired effect.

[0121] Comparative Example 2 used non-reactive thermoplastic acrylic resin as the carbon black grinding carrier, and its initial gloss still reached 96.5, indicating that the performance decline was not caused by obvious poor dispersion or appearance defects; however, the Taber retention rate after boiling in water was only 65.4%, which shows that there is a corresponding relationship between whether the grinding carrier can participate in the final crosslinking and the interface stability after water treatment.

[0122] Both Example 1 and Comparative Example 3 used the carbon black abrasive prepared in Preparation Example 1 and were subjected to the same UV curing conditions. The difference was that Comparative Example 3 used hot air treatment at 82°C for 10 min instead of near-infrared treatment in Example 1. The initial wear resistance of both was similar, but the highest temperature on the back side of the substrate in Comparative Example 3 reached 80.2°C, the duration of the back side temperature above 50°C was 690 s, and the warpage increment was 0.42 mm. The corresponding values ​​for Example 1 were 65.8°C, 118 s, and 0.12 mm, respectively. The above results indicate that, while achieving similar initial wear resistance, near-infrared treatment can utilize the absorption of near-infrared radiation by the carbon black-containing topcoat to allow the coating to reach the temperature required for thermal reaction more quickly, shorten the time the plastic substrate is at a higher temperature, and reduce the warpage caused by heating of the substrate.

[0123] Comparative Example 4 was first UV cured and then treated with near-infrared radiation. Its initial hardness reached 3H, but the Taber retention rate after boiling in water was 70.2%. Comparative Example 5 omitted the near-infrared treatment, indicating that the surface hardness cannot reflect the curing state of the coating depth and pigment interface alone. Using UV for rapid shaping or completely omitting the thermal reaction stage is not conducive to the performance retention after water treatment.

[0124] Although Comparative Example 6 used the same near-infrared and UV treatments as Example 1, it did not add HDI trimer. After boiling in water, the Taber retention rate was 58.9%, which can rule out the explanation that the near-infrared performance was improved only by solvent evaporation or physical drying. This indicates that the thermal crosslinking of hydroxy-isocyanate is an important chemical basis for the water resistance and scratch resistance in the near-infrared stage. Comparative Example 7 used only hydroxy acrylic resin as the grinding carrier. Its performance after boiling in water was better than that of the non-reactive carrier, but lower than that of Example 1. This shows that UV reactive grinding resin is beneficial for the further fixation of the grinding carrier in the subsequent photocurable network.

[0125] Comparative Example 8 had an initial gloss of 96.3, indicating that the existing solution could achieve a qualified initial high-gloss appearance; however, the Taber retention rate after boiling was 68.5%, and the back surface temperature was above 50°C for 552 seconds. In comparison, Example 1 improved the adhesion and abrasion resistance retention after water treatment without reducing the initial appearance, and shortened the time the substrate was at a higher temperature.

[0126] Experimental Example 2

[0127] After 24 hours of preparation, the fineness of each color paste was measured using a scraper fineness meter, and the results were analyzed using a rotational rheometer at 25°C and a shear rate of 20 s. -1 The apparent viscosity was measured, and the pigment paste was sealed and stored at 50℃ for 14 days. After being restored to 25℃ and left to stand for 24 hours, the fineness and viscosity were measured again. The bottom settling state was observed, and the viscosity change rate was calculated according to the following formula:

[0128]

[0129] Among them, R η η is the viscosity change rate, in %; η0 is the apparent viscosity before storage, in mPa·s; η1 is the apparent viscosity after storage, in mPa·s.

[0130] The results are shown in Table 5.

[0131] Table 5 Initial and thermal storage properties of carbon black abrasives

[0132]

[0133] As shown in Table 5, the initial fineness of Examples 1-3 and Comparative Examples 1-2 was no higher than 4.0 μm, and no hard sedimentation occurred after storage at 50°C, indicating that the reactive carrier did not sacrifice the dispersibility of carbon black. Comparative Example 2, using non-reactive resin, also had good pigment stability, but its final coating had significantly lower water resistance, further indicating that the effect of the present invention was not simply due to the improvement of pigment fineness. Comparative Example 1, after adding reactive resin after carbon black grinding, showed higher viscosity changes and coarsening after storage than Example 1. Comparative Example 3, without low-viscosity UV reactive grinding resin, had a higher initial viscosity, indicating that the UV-curable acrylate grinding carrier, in addition to participating in photocuring, also played a role in reducing grinding viscosity and maintaining pigment stability.

[0134] A 30±2 μm free film was prepared on a polytetrafluoroethylene (PTFE) plate and cured under the conditions specified in each example or comparative example. After curing for 24 h, the free film was peeled off, and ATR-FTIR was used to test the air side and the PTFE plate side, respectively, at a resolution of 4 cm⁻¹. -1 Scanned 32 times; acrylate double bond conversion rate based on 810 cm⁻¹ -1 Peak relative to 1725cm -1 Calculation of normalized area change of carbonyl peak; NCO conversion based on 2270 cm⁻¹ -1 Peak relative to 1725cm -1 The normalized area change of the peak is calculated, and the result is as follows: Figure 2 As shown.

[0135] For the gel fraction test, approximately 0.2000 g of cured free film was weighed and extracted in tetrahydrofuran at 23°C for 24 h, with the solvent changed every 6 h. The residue was vacuum dried at 60°C to constant weight. The gel fraction was the ratio of the dried residual mass to the initial mass. The wet mass was measured immediately after extraction. The swelling ratio was the difference between the wet mass and the dried residual mass divided by the dried residual mass. For the DSC test, 5-10 mg of cured film was heated in nitrogen at a rate of 10°C / min from 25°C to 180°C, and the residual exothermic reaction in the range of 60-180°C was integrated. For the cross-sectional microhardness test, a 10 gf load was applied and held for 10 s. Measurements were taken along the thickness direction of the topcoat at positions 3 μm, 8 μm, 13 μm, 18 μm, 23 μm, and 28 μm from the topcoat surface. Five measurements were taken at each depth and the average value was taken. The indentation hardness of Example 1, Comparative Examples 1-4, and Comparative Example 8 along the thickness direction of the topcoat is shown below. Figure 4 As shown in the figure, the results are shown in Table 6.

[0136] Table 6. Test results of cured film reaction degree and network integrity

[0137]

[0138] As shown in Table 6, the bottom C=C conversion rate of Example 1 was 88.6%, and the difference between the surface and bottom conversion rates was 5.6 percentage points. In Comparative Example 1, with the same final chemical composition, the bottom C=C conversion rate was only 81.8%, and the difference between the surface and bottom conversion rates increased to 11.7 percentage points. The NCO conversion rate and gel fraction also decreased from 91.8% and 94.8% to 82.0% and 90.3%, respectively. The structural results of this group are consistent with the changes in adhesion and abrasion resistance after boiling in Experiment 1, indicating that the addition of reactive resin during the grinding stage not only changed the pigment preparation process, but also affected the thermal reaction, photoreaction, and network integrity of the final coating.

[0139] The initial dispersibility of the pigment in Comparative Example 2 was similar to that in Example 1, but the bottom C=C conversion rate and gel fraction of the cured film were 79.6% and 87.5%, respectively, and the swelling ratio increased to 2.05. This indicates that the non-reactive abrasive carrier cannot form the same cross-linked network as the reactive carrier after being physically embedded. Its higher swelling ratio corresponds to the decrease in adhesion and wear resistance retention after boiling in water. Thus, a correlation was established between the reactivity of the abrasive carrier, network integrity, and performance after water treatment.

[0140] The gel fractions of Example 1 and Comparative Example 3 were 94.8% and 93.7%, respectively, which were at similar levels, indicating that both heating methods could initiate thermal crosslinking. However, Example 1 only needed 42 seconds to reach 80°C, while Comparative Example 3 needed 390 seconds to reach 80°C by hot air. Furthermore, the back temperature and warpage of the substrate in Comparative Example 3 were significantly higher. This indicates that the main purpose of selecting near-infrared radiation is to utilize the absorption of radiation by carbon black, allowing the carbon black-containing coating to reach the reaction temperature more quickly, thereby shortening the time that the entire plastic substrate is in a high-temperature environment.

[0141] Comparative Example 4, which underwent UV curing followed by NIR curing, achieved a surface C=C conversion rate of 95.2%, higher than Example 1. However, the bottom surface conversion rate was only 80.2%, resulting in a surface-to-bottom surface difference of 15.0 percentage points and a residual exothermic reaction of 8.2 J / g. This result indicates that a higher surface conversion rate does not equate to uniform curing. After UV curing for rapid surface shaping, subsequent thermal reactions cannot adequately compensate for the insufficient reaction at the bottom surface and pigment interface. In Comparative Example 5, when UV curing was performed only, the bottom surface conversion rate, NCO conversion rate, and gel fraction further decreased, verifying the necessity of the NIR preheating reaction stage.

[0142] In Comparative Example 6, without the addition of HDI, there was no measurable NCO conversion, and its gel fraction was only 82.7%, with a swelling ratio of 2.40. Although carbon black could still produce the same temperature rise under NIR, the coating did not achieve the same network integrity and water resistance as in Example 1, demonstrating that near-infrared heating must be combined with the reaction of hydroxy-isocyanate to achieve the main technical effect.

[0143] Comparative Example 7 used only hydroxyl acrylic resin to grind carbon black, achieving an NCO conversion rate of 91.0%. However, the bottom C=C conversion rate and gel fraction were lower than those of Example 1, indicating that simply enhancing thermal crosslinking was insufficient to allow the grinding carrier to fully enter the subsequent UV network. Example 1 used a composite grinding carrier of low-viscosity hydroxyl acrylic resin and UV-curable acrylate, which has reaction pathways in both the thermal curing and photocuring stages, thus obtaining a lower swelling ratio and a smaller surface-to-bottom hardness difference.

[0144] Comparative Example 8 showed a surface C=C conversion rate of 94.0%, indicating that the multi-photoinitiator and thermal / UV dual curing could achieve a good surface reaction; however, the bottom surface conversion rate was only 78.2%, the surface-to-bottom difference was 15.8 percentage points, and the gel fraction was 88.0%, all lower than Example 1. Combined with Experiment 1, it can be seen that the present invention does not simply replace ordinary hot air with near-infrared radiation, but further improves the curing state of the coating depth and pigment interface through the combined effect of pre-configuration of reactive grinding carrier, carbon black NIR heat absorption, and subsequent UV curing.

[0145] Examples 1-3 show that a mass ratio of low-viscosity hydroxyl acrylic resin to UV-curable acrylate abrasive carrier within the range of 70:30-85:15 can achieve high gel fraction and good post-water treatment performance. Among them, at a mass ratio of 80:20, the balance between pigment viscosity, NCO conversion, double bond conversion and abrasion resistance retention after boiling is better. Examples 4 and 5 further show that if the near-infrared temperature is too low, the treatment time needs to be extended, while if the temperature is too high, it may reduce DOI and increase warpage. Therefore, it is preferable to make the coating surface reach 79-85°C and hold it for 60-120 seconds.

[0146] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.

Claims

1. A waterproof, scratch-resistant, high-gloss coating for automotive interior parts, characterized in that, The product comprises a high-gloss black topcoat and a primer. By weight, the topcoat includes 12-25 parts of hexafunctional aliphatic polyurethane acrylate, 18-35 parts of difunctional aliphatic polyurethane acrylate, 5-15 parts of hydroxyl-functional aliphatic polyurethane acrylate, 1.5-4.5 parts of carbon black, 2-8 parts of low-viscosity hydroxyl acrylic resin, 0.5-3 parts of UV-curable acrylate grinding carrier, 0.3-1.5 parts of carbon black-specific polymeric dispersant, 6-16 parts of dipropylene glycol diacrylate, 3-10 parts of 1,6-hexanediol diacrylate, 1-6 parts of trimethylolpropane triacrylate, 1.5-3.0 parts of TPO-L, 0.3-1.2 parts of photoinitiator 184, and 0.1-0.6 parts of flow... The high-gloss black topcoat comprises a leveling agent, 0.05-0.5 parts defoamer, 0.1-1.0 parts scratch-resistant wax, 0.02-0.15 parts bismuth catalyst, 5-20 parts butyl acetate, and 2-12 parts aliphatic polyisocyanate. The low-viscosity hydroxyl acrylic resin and UV-curable acrylate grinding carrier form an interfacial contact dispersion with the carbon black particles, ensuring that the interfacial region of the carbon black particles simultaneously contains hydroxyl groups capable of reacting with isocyanate groups and acrylate groups capable of participating in UV curing. After curing, the high-gloss black topcoat has an NCO conversion rate of not less than 89.8%, a bottom acrylate double bond conversion rate of not less than 87.4%, and a difference between the surface and bottom acrylate double bond conversion rates of not more than 6.2 percentage points.

2. The waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 1, characterized in that: The primer comprises separately stored primer component A and primer component B. By weight, primer component A comprises 25-45 parts hydroxyl acrylic resin, 15-30 parts difunctional aliphatic polyurethane acrylate, 8-18 parts dipropylene glycol diacrylate, 1.0-3.0 parts TPO-L, 0.3-1.2 parts photoinitiator 184, 0.5-3.0 parts adhesion promoter, 0.1-0.6 parts leveling agent, 0.05-0.5 parts defoamer, and 10-25 parts butyl acetate. The sum of the weight parts of all raw materials in primer component A is 100 parts. Based on 100 parts by weight of primer component A, primer component B comprises 5-12 parts by weight of hexamethylene diisocyanate trimer.

3. The waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 1, characterized in that: The UV-curable acrylate abrasive carrier is an acrylate material containing two free radical polymerizable acrylate groups, with a solid content of not less than 98% and a viscosity of 80-250 mPa·s at 25°C.

4. The waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 1, characterized in that: The low-viscosity hydroxyl acrylic resin is a copolymer resin solution containing side-chain hydroxyl groups using butyl acetate as solvent. Its non-volatile content is 63-67%, its hydroxyl content based on non-volatile components is 2.8-3.2%, its acid value is 4-8 mgKOH / g, and its viscosity at 23-25℃ is 1.5-3.0 Pa·s.

5. The waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 1, characterized in that: The UV-curable acrylate abrasive carrier is a low-viscosity acrylate abrasive carrier containing two free radical polymerizable acrylate groups, with a solid content of not less than 98% and a viscosity of 80-250 mPa·s at 25℃.

6. The waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 1, characterized in that: The hydroxyl-functional aliphatic polyurethane acrylate is an aliphatic polyurethane acrylate oligomer containing both hydroxyl groups and free radical polymerizable acrylate groups. Its solid content is 55%-65%, its hydroxyl value is 20-40 mgKOH / g, and its viscosity at 25°C is 1000-2500 mPa·s.

7. The waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 1, characterized in that: The TPO-L is ethyl 2,4,6-trimethylbenzoylphenylphosphonate, the photoinitiator 184 is 1-hydroxycyclohexylphenyl ketone, the leveling agent is a polyether-modified polydimethylsiloxane type surface additive, the defoamer is a silicone-free polymer defoamer, and the scratch-resistant wax is micronized polyethylene wax.

8. A method for preparing a waterproof, scratch-resistant, high-gloss coating for automotive interior parts as described in any one of claims 1-7, characterized in that, Includes the following steps: S1: Mix the low-viscosity hydroxyl acrylic resin, UV-curable acrylate grinding carrier, carbon black-specific polymeric dispersant, 40%-60% of the total amount of dipropylene glycol diacrylate and 30%-50% of the total amount of butyl acetate, add carbon black for pre-dispersion and grinding, and grind until the fineness is no greater than 5μm to obtain reactive carbon black grinding material. S2: Add 6-functional aliphatic polyurethane acrylate, 2-functional aliphatic polyurethane acrylate, hydroxyl-functional aliphatic polyurethane acrylate, remaining dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, TPO-L, photoinitiator 184, leveling agent, defoamer, scratch-resistant wax, bismuth catalyst and remaining butyl acetate to the reactive carbon black abrasive. Mix, degas and filter to obtain topcoat component A. Mix topcoat component A with topcoat component B to obtain high-gloss black topcoat. S3: Mix hydroxyl acrylic resin, difunctional aliphatic polyurethane acrylate, dipropylene glycol diacrylate, TPO-L, photoinitiator 184, adhesion promoter, leveling agent, defoamer and butyl acetate, defoam and filter to obtain primer component A, mix primer component A with primer component B to obtain primer. S4: Spray the primer onto the surface of the automotive interior plastic substrate, control the dry film thickness of the primer to be 10-15μm, level it at 20-30℃ for 5-10min, then heat treat it at 60-75℃ for 5-10min, and then perform UV pre-curing after cooling. S5: Spray the high-gloss black topcoat onto the surface of the automotive interior plastic substrate that has been primed, control the dry film thickness of the high-gloss black topcoat to be 25-35μm, level it at 20-30℃ for 5-10min, and then flash dry it at 45-60℃ for 3-8min. S6: The high-gloss black finish after the flash drying is subjected to near-infrared irradiation, so that the surface temperature of the high-gloss black finish reaches 75-90 DEG C and is maintained for 60-120 s, within 30 s after the end of the near-infrared irradiation, first 365 nm ultraviolet light is used for irradiation, and then 395 nm ultraviolet light is used for irradiation, and the total ultraviolet irradiation energy is 900-1800 mJ / cm 2 , to obtain a waterproof and scratch-resistant high-gloss coating for an automotive interior part.

9. The method for preparing a waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 8, characterized in that: In step S1, the grinding base material is first stirred at 600-1000 r / min for 10-20 min, and then carbon black is added in batches under stirring at 1000-1500 r / min. The material is then pre-dispersed at 1500-2500 r / min for 20-40 min. The pre-dispersed material is then transferred into a sand mill and ground using zirconia beads with a diameter of 0.6-0.8 mm. The filling volume of the zirconia beads is 60-75% of the effective volume of the grinding chamber of the sand mill. The linear speed of the grinding rotor is 8-12 m / s, and the grinding temperature is 30-45℃.

10. The method for preparing a waterproof, scratch-resistant, high-gloss coating for automotive interior parts according to claim 8, characterized in that: In step S4, after the surface temperature of the primer after heat treatment is cooled to no higher than 35°C, it is first irradiated with 365nm ultraviolet light until the irradiation energy is 200-400mJ / cm. 2 Then, irradiate with 395nm ultraviolet light to an irradiation energy of 300-600mJ / cm. 2 After completing the UV pre-curing of the primer, in step S6, a near-infrared device with a peak wavelength of 950nm and an effective radiation band of 800-1200nm is used for irradiation. Within 30 seconds after the near-infrared irradiation ends, 365nm ultraviolet light is used to irradiate until the irradiation energy reaches 400mJ / cm². 2 Then, irradiate with 395nm ultraviolet light to an irradiation energy of 800mJ / cm. 2 .

Citation Information

Patent Citations

  • Colored dual-curing UV coating for automobile interior trim parts

    CN108997925A

  • Dual-curing highlight coating for automotive interior and preparation method and application of dual-curing highlight coating

    CN111534213A